Synthesis and biological evaluation of ortho-phenyl phenylhydroxamic acids containing phenothiazine with improved selectivity for class IIa histone deacetylases - Kai-Cheng Hsu; Yun-Yi Huang; Jung-Chun Chu; Yu-Wen Huang; Jing-Lan Hu; Tony Eight Lin; Shih-Chung Yen; Jing-Ru Weng; Wei-Jan Huang (Taylor & Francis Group, 2024)
Class IIa histone deacetylases (HDACs) have been linked to tumorigenesis in various cancers. Previously, we designed phenylhydroxamic acid LH4f as a potent class IIa HDAC inhibitor. However, it also unselectively inhibited class I and class IIb HDACs. To enhance the compound's selectivity towards class IIa HDACs, the ortho-phenyl group from the selective HDAC7 inhibitor 1 is incorporated into ortho position of the phenylhydroxamic acid in LH4f. Compared to LH4f, most resulting compounds displayed substantially improved selectivity towards the class IIa HDACs. Notably, compound 7 g exhibited the strongest HDAC9 inhibition with an IC50 value of 40 nM. Molecular modelling further identified the key interactions of compound 7 g bound to HDAC9. Compound 7 g significantly inhibited several human cancer cells, induced apoptosis, modulated caspase-related proteins as well as p38, and caused DNA damage. These findings suggest the potential of class IIa HDAC inhibitors as lead compounds for the development of cancer therapeutics.